Impact of Person-Organization-Fit on Patient Care Quality - Fozia Arshad, Sehrish Arshad, Razia Bano, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Person- organization -fit has great impact on patient care quality, without person-organization-fit patient care quality cannot be achieved. Today attention of health care organizations is diverted toward their benefit and they are not providing proper resources to staff nurses so, quality of patient care is compromised. Purpose of study: This research was done to determine impact of person-organization-fit on patient care quality. Methodology: A Quantitative, Descriptive, Cross sectional study done. Population was staff nurses of Services hospital Lahore, sample size was 150 with 5% of confidence error and 95% confidence interval. Research tool was adopted questionnaire on 5 points Likert scale (LS) with close ended questions. Descriptive statistics was used to measure demographic data. Linear regression was used to determine impact of person-organization-fit on patient care quality. Results: Study findings showed that there is strong positive relation between person- organization –fit and patient care quality. Moreover results showed reliability and validity of questions. 70% respondent’s values did not match their organizational values, 57.7% respondents not explaining procedure before perform,74% not encouraging patients for decision making, 62% respondents not involving patients in hospital care. Practical Implication: This study is beneficial for the organization as it will acknowledge health care organization about person-organization fit and patient care quality at their setting. It will help to improve patient care quality by making policies and rules to make their employees fit in an organization. This study will be beneficial for the employee as well as it will build them more professionally. They will be satisfied with their job performance and professional development. This study will be beneficial for organization as it will increase the productivity of organization. Conclusion: Study findings indicated that person -organization -fit has strong positive relation with patient care quality care quality; if person will be fit in organization patient care quality will be improved. Majority of respondents are not fit in their organization.70% nurses responded that their individual values did not match with their organizational values. Some respondents are providing some aspects of patient care quality but majority of respondents are missing important aspects of patient care quality. It is concluded that nurses are performing some aspects of patient care quality effectively but many other aspects are compromised due to person organization unfit. Person organization fit must be improved to improve patient care quality Keywords: POF Person- organization fit, Quality of patient care, Employees Satisfaction, LS Likert Scale, Productivity of organization.